EFFORTS TO IMPROVE THE ABILITY TO WRITE POETRY BY INDEPENDENT inquiry method SISWA KELAS VIII SMP NEGERI 6 MEDAN - Asnidar Asnidar (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2018)
Not everyone can write and create poetry. It requires a set of knowledge and abilities segmental and suprasegmental, so that people can string words. As a work of literature, poetry is a form of word play beautiful and orderly, so it is true what Robert Scholes said that literature is a show of words. Excellence is what makes the word knitting popular and favored literary readers. The words that emerge from these letters are the words chosen and represent feelings and thoughts. What about the students? Are they able to write or create poetry as poets? Writing poetry is a way for students to enable them to use the language contained sensitivity in him. In learning Indonesian language and literature, the ability to write poems very encouraging students to love their culture. Therefore, it is necessary concrete measures to assist and guide the students to be able to write and create good poetry. Among the available measures, the possibility inquiry method can help teachers to stimulate students were able to write poetry. Based on that, a class action research was conducted. This classroom action research helps teachers provide an answer that is appropriate inquiry method used in the teaching of writing poetry freely in the classroom.